Pareto Type IV SRGM using Order Statistics Approach (International Journal of Food and Nutritional Sciences, 2022)
In the modern society, the usage of computers is increasing day by day and is used in diverse areas. A lot of computer applications exist in almost every area in ever day life, reliability becomes a very extent, since in the matter of economy. Finally for producing software with high reliability, to develop a number of models and to make necessary measuring and its control of functionality. There are several software reliability growth models that can be used to forecast software system reliability.